The resurrection of tellurium as an elemental two-dimensional semiconductor - Qiu, Gang; Charnas, Adam; Niu, Chang; Wang, Yixiu; Wu, Wenzhuo; Ye, Peide D. (NPJ 2D materials and applications, 2022)
The graphene boom has triggered a widespread search for novel elemental van der Waals materials thanks to their simplicity for theoretical modeling and easy access for material growth. Group VI element tellurium is an unintentionally p-type doped narrow bandgap semiconductor featuring a one-dimensional chiral atomic structure which holds great promise for next-generation electronic, optoelectronic, and piezoelectric applications. In this paper, we first review recent progress in synthesizing atomically thin Te two-dimensional (2D) films and one-dimensional (1D) nanowires. Its applications in field-effect transistors and potential for building ultra-scaled Complementary metal–oxide–semiconductor (CMOS) circuits are discussed. We will also overview the recent study on its quantum transport in the 2D limit and progress in exploring its topological features and chiral-related physics. We envision that the breakthrough in obtaining high-quality 2D Te films will inspire a revisit of the fundamental properties of this long-forgotten material in the near future.